2009
DOI: 10.1097/eja.0b013e328318c666
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of etomidate–remifentanil and propofol–remifentanil sedation in patients scheduled for colonoscopy

Abstract: Etomidate-remifentanil administration for sedation and analgesia during colonoscopy resulted in more stable haemodynamic responses and shorter recovery and discharge times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
0
30
2
1
Order By: Relevance
“…It is believed that pain, distension of colon, stretching of the mesentery, and sedation regimen provoke these symptoms [1][2][3][4][5][6][7][8][9][10]. In our study, no vasovagal reactions were observed in any patients.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…It is believed that pain, distension of colon, stretching of the mesentery, and sedation regimen provoke these symptoms [1][2][3][4][5][6][7][8][9][10]. In our study, no vasovagal reactions were observed in any patients.…”
Section: Discussionmentioning
confidence: 40%
“…Greilich et al [6] showed that all patients who received remifentanil and midazolam for colonoscopy achieved readiness for discharge in 40 minutes. Toklu et al [7] compared remifentanil + propofol and remifentanil + etomidate in patients who underwent colonoscopy under sedation and reported that the mean discharge times were 32.8 and 24.6 minutes, respectively. The mean discharge time in our study was approximately 15 minutes (15.1 vs 15.7 minutes) in both groups, which was similar to the studies that showed that the mean discharge times were around 15 minutes using moderate sedation for colonoscopy [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deepa Kane et al 9 found delayed and prolonged sedation with propofol as compared to etomidate. This can be explained by the fact that the onset time after induction dose of propofol and etomidate is 40 s and 15-30 s, respectively while context sensitive half-life for propofol infusion up to 8 hrs is <40 min only.…”
Section: Discussionmentioning
confidence: 99%
“…olarak bulmuş-tur. Ancak, bu sonuçların aksine Toklu ve ark (13) remifentanil ile birlikte uygulanan propofolün derlenme odasına transfer süresini belirgin düzeyde uzattığını savunmuşlardır. Newson ve ark.…”
Section: Discussionunclassified